Application of Bayes Method To Design A Decision Support System Fof Determining The Status Of Permanent Employees In A Soft Beverage Company - Nurhasanah, Nurhasanah; Yuni Dharta, Firdaus; Shu, Efin; Rumianti, Chaerunnisa; Munizu, Musran (SEULANGA SYSTEM PUBLISHER, 2023)
The purpose of this study is to learn how to create a decision support system that can help with the process of deciding whether to hire contract workers on a permanent basis. The following methods of gathering data were employed in this study: literature review, interviews, and observation. The system development approach that the author employed to create this program was called rapid application development, or RAD. The decision support system that has been developed for contract employees to become permanent employees can assist and make it easier to see and read the results of contract employee assessments, according to the research results. This is because the system is quantitative and can generate reports that show the total numerical value of each criterion and sub-criteria for candidates for permanent employment. The system that has been developed has the ability to generate a report on contract employee assessments that presents contract employees in order of recommendation. The evaluation procedure and computation results can be accelerated with the use of a decision support system for contract employees who wish to become permanent employees. This way, the choice of whether to graduate or become a permanent employee can be made in less than seven days.